Does obesity mediate the relationship between diabetes and osteoporosis in Chinese elderly population?. Issue 3 (30th June 2021) - He, Pei; Zhong, Jiao; Zhu, Dong‐Cheng; Ge, Bing; Lei, Shu‐Feng; Deng, Fei‐Yan
Abstract: Objectives: Diabetes mellitus (DM), osteoporosis (OP), and obesity (OB) are three complex diseases. OB is associated with both DM and OP, but it is unclear whether OB mediates association between DM and OP. The study aimed to investigate the potential mediation effects of OB on association between DM and bone mineral density (BMD) by the causal inference tests (CIT). Methods: A total of 5682 Chinese aged over 65 years were enrolled in an ongoing cohort: Osteoporosis Preventive Project (OPP). Obesity‐related indexes, including body mass index (BMI), waist circumference, and waist circumference‐hip circumference‐ratio (WHR), and BMD at total hip (TH) and femur neck (FN) were measured. Results: Subjects with DM had significant greater values of age, weight, BMI, waist circumference, WHR, and BMD than non‐DM subjects. BMD at TH and FN was significantly associated with DM ( p  < 0.05) with adjustment of age both in males and females. Further CIT showed that OB‐related indexes (BMI, waist circumference, and WHR) are significantly mediators in the associations between DM and BMD in females, but not in males. Furthermore, the mediation effects of waist circumference were detected on DM and TH BMD in the females of normal‐weight group. Conclusions: Obesity‐related indexes, especially waist circumference, serve as significant mediator(s) between DM and OP in Chinese female elderly. Diabetes increases BMD by increasing obesity‐related indexes. The findings established the intermediate role of OB underlying the association between DM and OP in human population.